The Re-Emergence of Sovereign Spread in Emerging Countries in the Post-Covid–19 Economy - Sabri, Alipanah; Mészáros, Mercédesz; Kiss, Gábor Dávid (Public Finance Quarterly, 2022)
The Covid-19 crisis and its economic consequences for emerging countries have highlighted the role of robust, inclusive, and equitable elements of multiple contingency lines to keep these economies away from falling into a devastating cycle of rising sovereign spread. This study first summarizes the crisis-fighting performance of the IMF and eight major RFAs since the outbreak of Covid–19. Then our theoretical model focuses on the deterioration of market expectations (namely about future global economic growth, funding conditions in key currencies and public default) influence on the sovereign spread, by employing a structural panel Vector Autoregression. The results showed that sovereign spread depended not only on the global and local growth or the external funding environment but on the market sentiment as well. Also, the results pointed out the importance of financial supports by international actors like the IMF and partially the RFAs in managing the sovereign spread.